(untitled) (Baghdad Science Journal, 2014)
This research was carried out to evaluate the activity of crude juice of Olive on some cytogenetic parameters in mice like chromosomal aberration (CAs) and micronuclei formation(MN). The results showed that there was no significant difference between the crude juice (green and black)in CAs(3.77,4.10)and MN(0.25,0.25) in comparison with negative control (3.39,0.22)respectively. The interaction effect between the crude before and after treatment with mutagen MMC showed that the crude is one of the vital inhibitors of the mutagen by its ability in reducing the percentages of both the CAs and MN in bone marrow cells in mice.